Potensi Arkeologi Sebagai Identitas Budaya Suatu Bangsa (Suatu Kajian Antropologi) - Wattimena, Lucas (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Cultural resources in Indonesia, particularly in Maluku are invaluable. Therefore, it won’t be an exaggeration if we say that the cultural potency in Indonesia is rich and plentiful. The government’s concept on development nowadays is about how to develop every sector in Indonesia, particularly on culture and tourism. This is reasonable for the cultural identity of a nation reflects the identity of the nation itself, which can be measured by the various attraction, local wisdom, cultural resources (archaeological relic), language, and religion that it has. Then in Indonesia, those cultural products become a part of the multiculturalism in socio-cultural community.